2018
DOI: 10.1074/jbc.ra118.003081
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of novel binding sites for heparin in receptor protein-tyrosine phosphatase (RPTPσ): Implications for proteoglycan signaling

Abstract: Receptor protein-tyrosine phosphatase RPTPσ has important functions in modulating neural development and regeneration. Compelling evidence suggests that both heparan sulfate (HS) and chondroitin sulfate (CS) glycosaminoglycans (GAGs) bind to a series of Lys residues located in the first Ig domain of RPTPσ. However, HS promotes and CS inhibits axonal growth. Mutation of these Lys residues abolished binding and signal transduction of RPTPσ to CS, whereas HS binding was reduced, and signaling persisted. This acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…In agreement with these results, we found that LAR Ig1-3 was retained on a heparin column and that LAR Ig1-3 bound Hep-FITC with a nanomolar affinity. This is compatible with the values obtained for the affinity of PTPR for CS (K d = 11 nM; Shen et al, 2009) and for heparin (K d = 0.3 nM; Katagiri et al, 2018) considering that these values were obtained using immobilized ligands, whereas the K d measured here was for the components in solution. Furthermore, we found that Innohep induced a shift in hydrodynamic size for both LAR Ig1-3 and LAR FN5-8 while the chemically well defined pentameric LMWH drug Arixtra did not.…”
Section: Carbohydrate Bindingsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with these results, we found that LAR Ig1-3 was retained on a heparin column and that LAR Ig1-3 bound Hep-FITC with a nanomolar affinity. This is compatible with the values obtained for the affinity of PTPR for CS (K d = 11 nM; Shen et al, 2009) and for heparin (K d = 0.3 nM; Katagiri et al, 2018) considering that these values were obtained using immobilized ligands, whereas the K d measured here was for the components in solution. Furthermore, we found that Innohep induced a shift in hydrodynamic size for both LAR Ig1-3 and LAR FN5-8 while the chemically well defined pentameric LMWH drug Arixtra did not.…”
Section: Carbohydrate Bindingsupporting
confidence: 92%
“…This was confirmed by the MST measurements of FITC-Hep, which showed affinity in the low micromolar range. This is in contrast to the heparin affinity of the PTPR juxtamembrane domain, which was 0.6 nM (Katagiri et al, 2018). As for LAR Ig1-3 , analysis by SEC showed that Innohep was likely to induce oligomerization of LAR FN5-8 while Arixtra did not, indicating that the minimal sugar length for oligomerization is larger than five.…”
Section: Carbohydrate Bindingmentioning
confidence: 81%
See 3 more Smart Citations